Financial Performance of Moroccan Listed Companies: A Multidimensional Analysis of Internal, Macroeconomic, and Institutional Determinants Using Dynamic Panel Data - Asmae AMARHYOUZ; Jalal Azegagh (Qubahan Academic Journal)
This study aims to identify the main determinants of financial performance of non-financial companies listed on the Casablanca Stock Exchange. The research focuses on assessing how internal, macroeconomic, and institutional variables affect performance, using (ROA) and (ROE) as key indicators. Methodology: The empirical study covers 8 years from 2013 to 2020 and a balanced panel of 51 Moroccan listed companies. The explanatory variables fall into three categories: firm-specific factors (liquidity, size, age, growth opportunities, and capital structure), macroeconomic indicators (inflation rate, interest rate, exchange rate and GDP growth), and institutional quality (corruption index). To validate the robustness of the outcomes (heteroskedasticity, autocorrelation, and endogeneity), several panel data estimation techniques were applied, including pooled OLS, fixed effects models, and the Generalized Method of Moments (GMM). Findings: The results show that liquidity and growth opportunities have a significant and positive impact on performance, while age, firm size, and leverage exert a negative effect. Regarding external factors, inflation and interest rates are shown to be significant constraints to financial performance, whereas GDP growth and exchange rate fluctuations have a non-significant effect. The institutional factor (corruption index), displays only weak explanatory power. Practical implications: The findings provide valuable insights for corporate managers, investors, and policymakers by emphasizing the importance of sound internal financial management, particularly in terms of liquidity and investment strategies. Moreover, the study underlines the need for macroeconomic stability and institutional improvement to support firm performance in emerging markets as Morocco. Originality/value: To the authors' knowledge, empirical studies on the combined effects of internal, macroeconomic and institutional determinants of business performance in the Moroccan context are non-existent. This study contributes to bridging that gap by offering an integrated and dynamic approach to performance analysis, which may serve as a reference for future research on emerging capital markets.